Decision Support Tool for Sustainable Land Management: Integrating Stakeholders and WEFE Nexus. Landscape 2024 conference Humboldt university - Akramkhanov, Akmal; Verbist, Joren (2024)
The present presentation describes about Decision Support Tool (DST) which was developed to consider the difficult and complex interplay of the Water-Energy-Food-Ecosystem (WEFE) Nexus in Aral Sea Basin region through Best Worst Method (BWM).